2007
DOI: 10.1161/01.atv.0000254147.89321.cf
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-Mediated Expression of Tissue Factor Pathway Inhibitor-2 Inhibits Endothelial Cell Migration and Angiogenesis

Abstract: Objective-Extracellular matrix (ECM) remodeling during angiogenesis is accomplished through plasmin-dependent pericellular proteolysis and through the action of matrix metalloproteinases (MMPs). Because tissue factor pathway inhibitor-2 (TFPI-2), a Kunitz-type protease inhibitor with prominent ECM localization, inhibits plasmin and MMPs activity, we investigated the role of TFPI-2 in endothelial cell (EC) migration and angiogenesis. Methods and Results-Real-time polymerase chain reaction and immunostaining sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…While others have demonstrated apoptosis induction in EA.hy926 endothelial cells, as well as glioblastoma, malignant meningioma and prostate tumor cell lines through overexpression of TFPI-2 [11,[14][15][16][17], it is unclear whether these cells undergo apoptosis following exogenous application of either TFPI-2 or R24K KD1. To this end, we incubated human umbilical vein endothelial cells, a human colon carcinoma cell line (Colo-205) and a human bladder carcinoma cell line (J-82) with either vehicle, 1 lM TFPI-2, 1 lM R24K KD1 or 1 lM R24Q KD1 for 48 h. Following incubation, the cells were processed for EB/AO staining and immunoblotting of the cell lysate to quantify the level of activated caspase-3, since the activation of caspase-3 serves as a sensitive marker of apoptosis [20].…”
Section: Pro-apoptotic Effect Of Tfpi-2 On Other Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…While others have demonstrated apoptosis induction in EA.hy926 endothelial cells, as well as glioblastoma, malignant meningioma and prostate tumor cell lines through overexpression of TFPI-2 [11,[14][15][16][17], it is unclear whether these cells undergo apoptosis following exogenous application of either TFPI-2 or R24K KD1. To this end, we incubated human umbilical vein endothelial cells, a human colon carcinoma cell line (Colo-205) and a human bladder carcinoma cell line (J-82) with either vehicle, 1 lM TFPI-2, 1 lM R24K KD1 or 1 lM R24Q KD1 for 48 h. Following incubation, the cells were processed for EB/AO staining and immunoblotting of the cell lysate to quantify the level of activated caspase-3, since the activation of caspase-3 serves as a sensitive marker of apoptosis [20].…”
Section: Pro-apoptotic Effect Of Tfpi-2 On Other Cellsmentioning
confidence: 99%
“…In addition, overexpression of TFPI-2 in several highly invasive tumor cells has been shown to inhibit their growth, invasiveness, angiogenic and metastatic potential [6,[11][12][13][14]. Finally, recent studies have shown that adenovirus vector-mediated overexpression of TFPI-2 inhibits EA.hy926 endothelial cell migration and angiogenesis, and also increased apoptosis of these cells by over twofold [15].…”
Section: Introductionmentioning
confidence: 97%
“…The mouse Foxk1 cDNA was inserted under the control of the cytomegalovirus (CMV) promoter/enhancer upstream of an ires-GFP fragment to produce a bicistronic pAC shuttle plasmid (Ivanciu et al, 2007). To construct a negative control, no cDNA was inserted into this vector.…”
Section: Adenoviral Infectionmentioning
confidence: 99%
“…Downregulation of TFPI-2 expression has been related to pathophysiological processes such as inflammation, angiogenesis, atherosclerosis and tumor growth/ metastasis [30,74,75]. As a consequence of decreased MMP-2 activation, TFPI reduced ECM degradation, tumor growth and metastasis [76,83]. Thus, understanding the protease specificity of each Kunitz domain is biologically significant.…”
Section: Tissue Factor Pathway Inhibitor (Tfpi)mentioning
confidence: 99%